How can Europe solve its unemployment problem? - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
In continental Europe, the unemployment rate has risen continuously from a low level of below 3 percent in the early 1970s to more than 10 percent in the late 1990s. If those who are in governmental employment schemes and in early retirement are included, the unemployment rate runs as high as 20 percent in quite a few European countries, including France and Spain. The basic rule for a stable employment situation in an economy is: nominal wages should stay in line with labor productivity growth plus the increase in producer prices. In a situation of high unemployment, however, when the unemployed are to be integrated into the labor market, the productivity rule has to be modified: the increase in real wages should stay below the productivity growth rate until a satisfactory level of employment has been obtained. The most elegant approach to creating more employment is to improve labor productivity. If an economy succeeds in raising labor productivity, there is more scope for real wage increases or for more employment. We should, however, not overestimate the potential of an economy to increase labor productivity. If we want to integrate the unemployed, average labor productivity in the economy is likely to decrease. We should be realistic enough as to expect trends in Europe to be similar to those in the United States, where labor productivity per hour has increased by less than 1 percent per year since 1980. The task for Europe is to change the institutional setup of labor relations, to move wage formation closer to the market process, and to allow greater wage differentiation. It is unlikely that the "social partners", i.e., the trade unions and employers' associations, will be able to change the rule system sufficiently. Therefore, it is necessary to change the legal rules, especially those in favor of the unemployed, for instance, by introducing a legal right for each individual to enter the labor market at a wage of his or her choice. If continental Europe wants to reduce unemployment, it will have to change the impact of the welfare state. With respect to the level of benefits provided by unemployment and health insurance, a distinction should be made between large risks and small risks for the individual. Such a distinction between large and small risks would allow the costs of the social security system to be reduced, thus lowering the tax on labor. Insurance against large risks would be mandatory, small risk coverage would be optional. With respect to financing the welfare state, more choice should be given to the individual as concerns the insurance coverage that he/she desires. One serious issue concerning social welfare payments is determining the extent to which the level of social welfare benefits should be scaled down for those who are able to work in order to increase the incentive to work and the intensity of the search for work. A related issue is whether unemployment benefits should be reduced in their level or in the length of time they are paid in order to intensify the job search and reduce the reservation wage. Shifting the employment issue to the EL) level would take attention away from the need to decentralize wage formation, i.e., to negotiate wages at the level of firms. It would be an incentive not to undertake the necessary steps to solve national unemployment problems and it would shift the financial burden to those countries that are successful in reducing unemployment. It would elevate the national labor market cartels to the EU level and it would blur the lines of responsibility. National governments would shift their responsibility to the EU level. This would be an extremely dangerous development for European integration because the European cause would become the scapegoat of failed national policies.
Keywords: 330; Arbeitslosigkeit; Beschäftigung; Lohnpolitik; Arbeitsproduktivität; Arbeitsmarktflexibilisierung; Sozialreform; Lohnstruktur; Arbeitslosenversicherung; EU-Staaten; Westeuropa